Environmental assessment of farm-scaled anaerobic co-digestion for bioenergy production. (July 2015) - Lijó, Lucía; González-García, Sara; Bacenetti, Jacopo; Negri, Marco; Fiala, Marco; Feijoo, Gumersindo; Moreira, María Teresa
Highlights: Anaerobic monodigestion and codigestion were compared. The environmental advantages of suitable waste management were proved. The use of cereal crops as feedstock improves biogas yield. Cultivation step implies the most important environmental hotspot. Digestate management options were evaluated. Abstract: The aim of this study was to assess the environmental profile of a bioenergy system based on a co-digestion plant using maize silage and pig slurry as substrates. All the processes involved in the production of bioenergy as well as the avoided processes accrued from the biogas production system were evaluated. The results evidenced the environmental importance of the cultivation step and the environmental credits associated to the avoided processes. In addition, this plant was compared with two different plants that digest both substrates separately. The results revealed the environmental benefits of the utilisation of pig slurry due to the absence of environmental burdens associated with its production as well as credits provided when avoiding its conventional management. The results also presented the environmental drawbacks of the utilisation of maize silage due to the environmental burdens related with its production. Accordingly, the anaerobic mono-digestion of maize silage achieved the worst results. The co-digestion of both substrates was ranked in an intermediate position. Additionally, three possible digestate management options were assessed. The results showed the beneficial effect of digestate application as an organic fertiliser, principally on account of environmental credits due to avoided mineral fertilisation. However, digestate application involves important acidifying and eutrophicating emissions.